2012
DOI: 10.1371/journal.pone.0037391
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Iron Overload and Iron Deficiency on Liver Hemojuvelin Protein

Abstract: IntroductionHemojuvelin (Hjv) is a key component of the signaling cascade that regulates liver hepcidin (Hamp) expression. The purpose of this study was to determine Hjv protein levels in mice and rats subjected to iron overload and iron deficiency.MethodsC57BL/6 mice were injected with iron (200 mg/kg); iron deficiency was induced by feeding of an iron-deficient diet, or by repeated phlebotomies. Erythropoietin (EPO)-treated mice were administered recombinant EPO at 50 U/mouse. Wistar rats were injected with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 40 publications
2
10
1
Order By: Relevance
“…Despite prior studies showing that HJV liver membrane protein expression itself does not appear to be regulated by iron in mice and rats (38), our data have shown that in response to iron overload, translational repression mediated by the human HJV uORFs is significantly relieved in hepatic HepG2 cells (Fig. 5 and 6).…”
Section: Discussioncontrasting
confidence: 99%
“…Despite prior studies showing that HJV liver membrane protein expression itself does not appear to be regulated by iron in mice and rats (38), our data have shown that in response to iron overload, translational repression mediated by the human HJV uORFs is significantly relieved in hepatic HepG2 cells (Fig. 5 and 6).…”
Section: Discussioncontrasting
confidence: 99%
“…Insights from pregnancy‐induced erythropoiesis in women also suggest that soluble HJV may act as an hepcidin suppressor . Such hypothesis is however challenged by other data indicating that HJV gene is not modulated by Epo and that hepatocyte membrane HJV is not a critical determinant of hepcidin expression . In line with the latter, our data demonstrate that soluble HJV, which is not influenced by Epo (even at high dose), is not a mediator of Epo‐induced hepcidin suppression in humans.…”
Section: Discussionsupporting
confidence: 67%
“…Furthermore, at least 3 other proteins play roles by interacting between BMPs and the BMP receptor. The first protein is hemojuvelin (HJV) a glycosylphosphatidylinositol-linked membrane protein [41], the second is Mt2 [42], which regulates the levels of membrane-bound HJV, and the third is neogenin, a ubiquitously expressed transmembrane protein with multiple functions [43,44,45,46,47,48]. The gene of Mt2 carries several polymorphisms that have been linked to iron metabolic parameters, notably in patients presenting with iron-refractory iron-deficient anemia [49,50,51,52,53,54,55,56,57,58].…”
Section: Hepcidin; the Queen Of ‘Ironomics'mentioning
confidence: 99%